Normal Families and Growth of Meromorphic Functions with Their Kth Derivatives. (3rd June 2018) - Qi, Jianming; Meng, Fanning; Yuan, Wenjun
Abstract : Relying on the normal family theory, we mainly study uniqueness problems of meromorphic functions and theirk th derivatives and estimate sharply the growth order of their meromorphic functions. Our theorems improve some previous results.